LEGAL CONSEQUENCES FOR TAX CRIMES WITH FICTITIOUS TAX INVOICES - Edwin Sulasdjono Subroto; Dudik Djaja Sidarta; Noenik Soekorini (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2024)
This research aimed to examine the legal implications of tax fraud involving fictitious tax invoices by businesses and to examine the factors that judges take into account when imposing criminal penalties on those who use fictitious tax invoices in cases such as Decision Number523/Pid.Sus/2021/PN Cikarang, Decision Number 1227/Pid.Sus/2021/PN Jkt.Utr, and Decision Number 926/Pid.Sus/2019/PN Jkt.Utr. This study pertains to normative legal research, utilizing the statute approach and conceptual approach. Primary legal resources for this research consist of Law No. 7 of 2021 and Law No. 28 of 2007, while Secondary Legal Materials refer to data from media and literature sources. Collection of legal research materials through library research with legal material analysis techniques with descriptive analysis. The study findings demonstrate that companies engaging in tax fraud through fake tax invoices may face criminal charges under Article 39A of Law No. 7 of 2021. The penalties could range from a minimum of 2 years in prison to a maximum of 6 years, as well as fines equal to at least double the tax amount listed on the fraudulent invoices. These penalties apply to cases where there is evidence of tax evasion, tax collection, deductions, or payments being manipulated. Then the Judge's Consideration in Imposing Criminal Sanctions on Perpetrators of the Criminal Act of Using Fictitious Tax Invoices by Corporations in the Decision is in accordance with Article 39A of Law No. 7 of 2021.